Spatial variability analysis of the population distribution of Riyadh City in 2024 using geographic information systems (GIS) (The International Journal of Educational Sciences and Arts, 2026)
Studying population distribution is a key indicator of socio-economic development across most regions, given the close interconnectedness of local communities. Population characteristics remain fundamental in shaping development goals and evaluating progress toward strategic objectives. This study analyzes the spatial variation in the population distribution of Riyadh in 2024 using Geographic Information Systems (GIS). It aims to identify the geographical patterns of population distribution in the city and assess their spatial characteristics within the urban area. The study adopts a descriptive–analytical approach, employing cartographic representation and several quantitative statistical methods, including mean variance, measures of central tendency, standard distance, directional distribution, population density, and correlation coefficients. The findings indicate that the population of Riyadh in 2024 reached 7,138,215 individuals, accounting for 20.2% of Saudi Arabia’s total population. The population is largely concentrated in the city center and its eastern sectors, particularly in the municipalities of Al Rawdah, Al Malaz, Al Batha, Al Ulya, Al Ma’athar, Al Deera, and Al Rijaa. Together, these municipalities host approximately 3,196,726 residents, representing 44.7% of the city’s total population. The study recommends revisiting urban planning processes in Riyadh, with a focus on developing areas characterized by low development indicators and limited services, and enhancing human and public infrastructure to make them more attractive to residents and to support potential urban redistribution.
Keywords: Spatial Yariation; Population Distribution; Workforce Population; Riyadh City